2017
DOI: 10.1161/circimaging.117.006568
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Microvascular Obstruction

Abstract: During the past decades, advances in percutaneous coronary intervention and antithrombotic therapy have improved the prognosis of patients with ST-segment-elevation myocardial infarction (STEMI).1 However, in a substantial number of STEMI patients, myocardial perfusion remains impaired despite successful recanalization of the infarct-related epicardial coronary artery, and this scenario has been shown to increase the risk of future cardiovascular events.2 Therefore, coronary microcirculation has been identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…These findings are supported by the association of EAT with MVO and ST-deviation. Both parameters mirroring disturbed microcirculation [ 32 ], correlate with infarct size [ 30 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings are supported by the association of EAT with MVO and ST-deviation. Both parameters mirroring disturbed microcirculation [ 32 ], correlate with infarct size [ 30 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…MVO detected by CMR has the best predictive value for adverse LV remodeling and clinical outcomes. 14 …”
Section: Discussionmentioning
confidence: 99%
“…Several trials consistently showed that MVO has the best predictive value above all CMR parameters. Its predictive value resulted to be additive to clinical scores, left ventricular ejection fraction, and infarct size ( 28 , 29 ). Moreover, the extent of MVO areas has been demonstrated to better stratify prognosis than the sole assessment of its presence ( 28 , 30 ).…”
Section: Introductionmentioning
confidence: 96%